Assessing bioavailable fraction and bioconcentration factors of Cd and Zn in young silage maize under different P fertilization and crop rotation. Issue 1 (1st January 2021) - Nino Savala, Andrea Giovanna; Franzaring, Jürgen; Zhong, Zhuang; Li, Huafen; Fangmeier, Andreas
ABSTRACT: The bioconcentration factors and two methods for estimating the bioavailable fraction of Cd and Zn were evaluated to their concentrations in young silage maize under different phosphate and crop management. The DGT technique and the extraction method with NH4 NO3 indicated a moderate correlation to Cd levels in maize. After the first crop rotation, Cd bioavailability increased under high-banded P fertilization, indicating a potential accumulation of labile Cd in arable soil in a short period of time. This effect was not visible in the Cd uptake by the following maize crop. P placement strongly affected Zn concentration in maize. A previous legume crop enhanced Cd bioavailability and Cd uptake compared with a wheat crop rotation. Particular attention should be paid to interactions between essential and toxic elements (P, Zn, and Cd), P overfertilization, and high Cd contents in P fertilizers even in the short term to prevent accumulation of labile Cd in soil-maize systems.